Tobacco Use among Adult Muslims in the United States. (3rd July 2019) - Attarabeen, Omar; Alkhateeb, Fadi; Larkin, Kevin; Sambamoorthi, Usha; Newton, Michael; Kelly, Kimberly
Abstract: Background: Compared with the general United States (US) population, Muslims in the US exhibit elevated rates of tobacco use. As a result, they might be at a higher risk for preventive disease and premature death as compared with the general US population. Objective: This study investigated the Social Cognitive Theory (SCT) factors that are associated with tobacco use among a sample of adult Muslims in the US. Methods: Data were collected (November 2016–March 2017) using a cross-sectional, on-line survey from a convenience sample of adult (≥ 18 years) US Muslims. Participants with a lung cancer history were excluded. Associations between SCT factors and tobacco use were investigated with bivariate analyses and multinomial logistic regression models. Results: Eligible participants ( n  = 271) from 30 states completed the survey; 52.8% reported current tobacco use. A higher rate of current tobacco use was reported by men (62.8%) as compared to women (41.3%), x 2 (1, N  = 271) = 12.49, p  < .001. In terms of cognitive factors, individuals who (1) expected more personal consequences for tobacco use on health, and (2) had more confidence regarding ability to abstain from tobacco use, were less likely to report current tobacco use. In terms of environmental factors, individuals whose family members did not use tobacco were less likely to report current tobacco use. Conclusion: The study findings suggest that family-oriented interventions emphasizing self-efficacy and personal consequences to prevent tobacco use can potentially be effective in reducing tobacco use rates in the adult US Muslim population.